Experimental and numerical investigation on structural damping behavior of corroded Fe-SMA - Yuanmu Li; Zhe-Xi Zhang; Cheng Fang; Guohui Cao; Cuiling Ran; Haihui Ren; Yuelin Zhang (Engineering Structures, 2026)

Chiral Ratiometric Fluorescent Silicon Nanoparticles for “Turn-on” Enantioselective Recognition of Tryptophan - Chen Liu; Yaning Duan; Cancan Lu; Yu Fu; Cuiling Ren; Hongli Chen (Journal of Fluorescence, 2026)

New silicon nanoparticles for “turn-on” detection of salicylaldehyde in food based on ESIPT mechanism - Jialu Zhang; Yu Fu; Peng Chen; Bowen Liu; Cuiling Ren (Food Chemistry, 2025)

Red Emission Carbon Nanoparticles Which Can Simultaneously Responding to Hypochlorite and pH - Yinghua Liu; Wenxiu Duan; Huiqing Li; Jiang Wu; Dan Liu; Jiaying Mi; Shengda Qi; Cuiling Ren; Hongli Chen (Journal of Fluorescence, 2023)

Construction of dual exponential amplification accompanied by multi-terminal signal output method for convenient detection of tumor biomarker FEN1 activity - Wei Chen; Huige Zhang; Yanning Zhang; Meiyi Hui; Hongli Chen; Cuiling Ren; Duolong Di; Haixia Zhang (Analytica Chimica Acta, 2023)

Discovery of potential anti-SARS-CoV-2 drugs based on large-scale screening in vitro and effect evaluation in vivo - Haoran Peng; Cuiling Ding; Liangliang Jiang; Wanda Tang; Yan Liu; Lanjuan Zhao; Zhigang Yi; Hao Ren; Chong Li; Yanhua He; Xu Zheng; Hailin Tang; et al. (Science China Life Sciences, 2022)

HMGB1: an important regulator of myeloid differentiation and acute myeloid leukemia as well as a promising therapeutic target - Lulu Liu; Jingjing Zhang; Xianning Zhang; Panpan Cheng; Lei Liu; Qian Huang; Haihui Liu; Saisai Ren; Peng Wei; Cuiling Wang; Cuiyun Dou; Lulu Chen; et al. (Journal of Molecular Medicine, 2021)
High mobility group box 1 (HMGB1) is a non-histone nuclear protein which has been intensively studied in various physiological and pathological processes including leukemia. Here in this study, we further demonstrated that HMGB1 presents higher expression in the bone marrow mononuclear cells of acute myeloid leukemia (AML) patients compared with the normal controls and contributes to the AML pathogenesis and progression by inhibiting apoptosis, facilitating proliferation, and inducing myeloid differentiation blockade of AML cells. Mechanistic investigation revealed that transforming growth factor beta-induced (TGFBI) acts as a potential downstream target of HMGB1 and lentivirus-mediated knockdown of TGFBI expression impaired phorbol-12-myristate-13-acetate (PMA) and all-trans retinoic acid (ATRA)–induced myeloid differentiation of AML cell lines. On the other hand, chidamide, an orally histone deacetylase inhibitor, decreases HMGB1 expression significantly in AML cells with concomitant upregulation of TGFBI expression, and confers therapeutic effect on AML by inducing cell differentiation, apoptosis and inhibiting cell proliferation. In conclusion, our findings provide additional insights that HMGB1 is a promising therapeutic target of AML, and also present experimental evidence for the clinical application of chidamide as a novel agent in AML therapy by downregulating HMGB1 expression. Key messages HMGB1 induces cell proliferation and myeloid differentiation blockade and inhibits apoptosis of AML cells. TGFBI acts as a potential target of HMGB1. Chidamide, a selective HDAC inhibitor, confers promising therapeutic effect for AML via downregulating HMGB1 expression.